In Silico Study of Gaseous Air Pollutants Effects on Human Atrial Tissue (2019)
Exposure to gaseous air pollutants such as carbon monoxide (CO), nitric oxide (NO) and sulfur dioxide (SO2) promotes the occurrence of cardiac diseases. Investigations have shown that CO and SO2 block the calcium channel (ICaL) of myocytes. The SO2 also increases the sodium channel (INa), the transient outward (Ito) and inward rectifying (IK1) potassium currents. The NO blocks INa and increases ICaL. We developed concentration dependent equations to simulate the gaseous pollutants effects on the ionic currents. They were incorporated in the Courtemanche model of human atrial cell and in a 2D tissue model. A train of 10 stimuli was applied. The action potential duration (APD) was measured. S1-S2 cross-field protocol was applied to initiate a rotor. The CO and SO2 concentrations from 0 to 1000 uM and NO concentration from 0 to 500 nM were implemented. Six concentration combinations were simulated (cases 1 to 6). The gaseous air pollutants caused an APD shortening and loss of plateau phase of the action potential in a fraction that increases as the pollutant concentration increases. When the highest concentration was applied, the APD decreased by 81%. In the 2D model, from case 4 conditions it was possible to generate rotor, propagating with high stability. These results show pro-arrhythmic effects of gaseous air pollutants. © 2019 Creative Commons.